Clinical significance and role of coinfections with respiratory pathogens among individuals with confirmed severe acute respiratory syndrome coronavirus-2 infection - Trifonova, Ivelina; Christova, Iva; Madzharova, Iveta; Angelova, Svetla; Voleva, Silvya; Yordanova, Ralitsa; Tcherveniakova, Tatiana; Krumova, Stefka; Korsun, Neli (Frontiers in Public Health, 2022)
Introduction This study aimed to determine the prevalence, viral profile, and clinical features of coinfections with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) and other respiratory viruses. Methods Nasopharyngeal samples and clinical data of 221 hospitalized patients and 21 outpatients were collected and analyzed. Real-time reverse transcription-polymerase chain reaction was used to detect SARS-CoV-2, influenza virus, respiratory syncytial virus (RSV), human metapneumovirus (HMPV), parainfluenza virus (PIV) 1,2,3, rhinovirus (RV), adenovirus (AdV), bocaviruses (BoV), and seasonal coronaviruses (OC43, 229E, NL63, and HKU1). Viral load was determined by capillary electrophoresis. Results From November 2020 to mid-March 2022, 242 SARS-CoV-2 positive patients were tested for seasonal respiratory viruses, and 24 (9.9%) cases of coinfections were detected. The distribution of viruses involved in cases of coinfections were as follows: HMPV (n = 6; 25%), RSV (n = 4;16.7%), AdV (n = 4; 16.7%), BoV (n = 4; 16.7%), PIV3 (n = 2; 8.3%), influenza A (H3N2; n = 2; 8.3%), RV (n = 1; 4.62%), and RV+BoV (n = 1; 4.62%). The proportion of detected coinfections with SARS-CoV-2 was highest in children aged 0–5 years (59%), followed by those >65 years (33%). In specimens with detected coinfection, the viral load of influenza was higher than that of SARS-CoV-2, and the mean viral load of SARS-CoV-2 was higher than that of the other respiratory viruses. C-reactive protein (CRP) and lymphocytes count in co-infected patients >65 years of age were on average higher than in children <16 years of age (mean CRP of 161.8 ± 133.1 mg/L; 19.7 ± 3.09% vs. mean 6.9 ± 8.9 mg/L, 0.9 ± 3.1%; p < 0.01). Patients >65 years of age co-infected with SARS-CoV-2 and other respiratory viruses had longer hospital stays than those <16 years of age (mean 9 ± 3.96 days vs. 5.44 ± 1.89 days; p = 0.025). The combination of AdV and SARS-CoV-2 is fatal for patients aged >65 years. Conclusion In patients aged >65 years, coinfection with SARS CoV-2 and other respiratory viruses, together with concomitant diseases, causes worsening of the clinical picture and complications, and can be fatal. Screening of patients with SARS CoV-2 for other respiratory viruses is needed to select appropriate treatments and prevent a fatal outcome of the disease.